Exploratory factor analysis in the measurement of the competencies of older people - Wiktorowicz, Justyna (Eksploracyjna analiza czynnikowa w ocenie kompetencji osób starszych, 2016)
Competencies are a crucial factor of professional position and career development. The aim of this paper is the assessment of the competencies of people in late productive age using exploratory factor analysis. The second point is the critical review of the theory and practice on exploratory factor analysis. The empirical analysis is based on the Study of Human Capital data. The survey results confirm the necessity of the factor analysis in research in the area of human capital in the context of ageing. The constructed synthetic indicators allowed for a synthetic assessment of the competencies of Poles aged 50-59/64. The results of the conducted analysis confirm the large significance of all the 24 analysed competencies. The competencies of Poles aged 50-59/64 were decomposed into three groups: (1) soft competencies and physical fitness (2) computer skills and (3) availability and technical competencies
Ekonometria = Econometrics, 2016, Nr 4 (54), s. 48-60
Keywords: exploratory factor analysis; competencies; ageing; eksploracyjna analiza czynnikowa; kompetencje; starzenie się